(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article deals with that in the context of modern educational demands, nonverbal communication plays a vital role in professional preparation, especially for students in the field of physical education, where bodily expression, gestures, facial expressions, and posture form the core elements of communication. This article explores the importance and urgency of developing nonverbal communicative competence among future physical education professionals. It outlines the theoretical foundations of nonverbal communication, analyzes current challenges in higher education programs, and presents practical strategies to enhance nonverbal skills in student-teachers. The study highlights how improved nonverbal competence contributes to more effective teaching, better student engagement, and enhanced professional identity in the physical education domain.